2018
DOI: 10.1016/j.pcad.2018.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High Intensity Interval Training on Cardiac Function in Children with Obesity: A Randomised Controlled Trial

Abstract: Twelve weeks of HIIT and MICT were superior to nutrition advice only for improving resting LV systolic function in obese children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 38 publications
0
31
0
2
Order By: Relevance
“…Study characteristics are presented as mean ± SD unless otherwise stated. Eighteen effects from 17 RCTs [11,12,13,14,15,16,18,19,20,21,22,23,24,25,26,27,28] of 563 participants were included in the review (Table 1). Of the 17 included studies, 10 enrolled obese subjects [11,12,13,16,20,21,23,26,27,28], 1 included normal weight and obese subjects [39], and 6 included normal weight subjects [14,18,19,22,24,25].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Study characteristics are presented as mean ± SD unless otherwise stated. Eighteen effects from 17 RCTs [11,12,13,14,15,16,18,19,20,21,22,23,24,25,26,27,28] of 563 participants were included in the review (Table 1). Of the 17 included studies, 10 enrolled obese subjects [11,12,13,16,20,21,23,26,27,28], 1 included normal weight and obese subjects [39], and 6 included normal weight subjects [14,18,19,22,24,25].…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, a number of experimental studies compared the effects of HIIT and MICT on CRF in children and adolescents, but the findings were inconsistent and inconclusive. Some intervention studies demonstrated that HIIT intervention stimulated significant increases in relative CRF when compared with MICT [11,12,13,14], while other studies did not observe any difference between these two methods [15,16,17,18,19,20,21,22,23,24,25,26,27,28]. Although there have been some systematic review suggested that the effect of HIIT on CRF is better than MICT [29,30], they focused on obese populations [30], or compared effect sizes with a non-exercise control group rather than a MICT group [31].…”
Section: Introductionmentioning
confidence: 99%
“…Aerobic exercise training is able to ameliorate dyslipidemia, insulin resistance, endothelial function, and inflammatory status [ 230 ]. It is well known that exercise training exerts beneficial effects in healthy [ 231 ] and in individuals with SAH [ 232 ], T2D [ 233 ], obesity [ 234 , 235 ], cancer [ 236 ], coronary heart disease [ 237 ], and chronic heart failure [ 238 ].…”
Section: Exercise and Cardiovascular Protectionmentioning
confidence: 99%
“…Supplementary materials can be found at . References [ 231 , 234 , 241 , 244 , 246 , 247 , 248 , 249 , 250 , 251 , 253 , 254 , 255 , 256 , 257 , 258 , 259 , 260 , 261 , 262 , 269 , 273 , 274 , 275 , 278 , 279 , 284 , 287 , 288 , 290 ] are cited in the supplementary materials.…”
mentioning
confidence: 99%
“…(A legtöbb labdajáték, a fogócska interval jellegű terhelést kíván, kellő szervezéssel és motivációval HIIT.) A kövér gyerekek HIIT-edzése -kontrollcsoportként MIC-edzése -4 × 4 perces, 90% körüli pulzusszámmal, heti három alkalommal, illetve 44 perc 65% körüli pulzusszámmal -egyaránt normalizálta a bal kamra nyugalmi szisztolés szöveticsúcs-sebességét 1, illetve 0,7 m/ mp-cel [40].…”
Section: Interval Edzés Egyéb Betegségek Eseténunclassified